Cognition and behavior in multiple sclerosis - DeLuca, John, 1956-; Sandroff, Brian M. (American Psychological Association, 2018)
"This volume consists of 15 stand-alone chapters that each address an important area pertaining to cognition and behavior in persons with MS. The first section of this textbook involves the latest characterization of MS-related cognitive impairment, with chapters on assessment and neuroimaging (i.e., structural and functional neuroimaging). The second section primarily involves the latest research on the mental health/behavioral correlates and consequences of MS-related cognitive impairment. This includes chapters on depression, neuropsychiatric disorders, fatigue, personality problems, activities of daily living, employment, and economic impact, respectively, and cognition in MS. The third section involves a chapter on pediatric-onset MS. This textbook concludes with a section on treatment approaches for MS-related cognitive impairment. This includes separate chapters on pharmacology, cognitive rehabilitation, exercise and physical activity, and cognitive reserve. The first edition of <xh:i>Cognition and Behavior in Multiple Sclerosis</xh:i> provides readers with a collection of the latest research by top scientists, pertaining to a largely understudied aspect of MS. By comprehensively addressing the correlates, consequences, and treatment of cognitive impairment in MS, it is our hope that this volume inspires new lines of clinical and behavioral research to improve the lives of those living with the disease, considering the common, burdensome, and challenging nature of cognitive impairment."--Preface. (PsycINFO Database Record (c) 2018 APA, all rights reserved)